A Comprehensive Analysis of the Small GTPases Ypt7 Involved in the Regulation of Fungal Development and Secondary Metabolism in Monascus ruber M7 - Liu, Jiao; Lei, Ming; Zhou, Youxiang; Chen, Fusheng (Frontiers in Microbiology, 2019)
Ypts (yeast protein transports)，also called as ras-associated binding GTPases (Rab), are the largest group of the small GTPases family, which have been extensively studied in model eukaryotic cells and play a pivotal role in membane trafficking, while this study showed potential regulation role of Ypts in fungi. One of Ypts, Ypt7 may be involved in fungal development and secondary metabolism, but the exact mechanism still exists a controversy. In current study, the functions of a Monascus ypt7 homologous gene (mrypt7) from Monascus ruber M7 was investigated by combination of gene-deletion (△mrypt7), overexpression (M7::PtrpC-mrypt7) and transcriptome analysis. Results showed that the radial growth rate of △mrypt7 was significantly slower than M. ruber M7, little conidia and ascospores can be observed in △mrypt7, but the yield of intracellular secondary metabolites was dramatically increased. Simultaneously, the mrypt7 overexpression strain possessed similar capacity for sporulation and secondary metabolism observed in M. ruber M7. Transcriptome results further illustrated that mrypt7 could coordinate with numerous genes involved in the vegetative growth, conidiogenesis, secondary metabolism biosynthesis and transportation of M. ruber M7. Combined with the similar effect of Ypt7 homologs on other fungi, we propose that Ypt7 works more like a global regulatory factor in fungi. To our knowledge, it is the first time to investigate Ypt7 functions in Monascus. It could also improve the understanding of Ypt7 functions in fungi.